Electronic structure and soft magnetic properties of Se/FeSiAl (110) films - Cardoso Schwindt, Virginia Araceli (2015)
The Se adsorption at different coverages on DO3 FeSiAl(110) surface is studied using density functional theory (DFT). Se adsorption is favorable in almost all surface high-symmetry sites, except for the bridge site formed by Fe–Si atoms. The most stable is a hollow site formed by four Fe atoms with adsorption energy of −5.30 eV. When the coverages increase, the energies decrease in the case of hollow sites. The surface present a reconstruction after Se adsorption, being the most important at 1/2 ML. The local magnetic moment for Fe atoms increase for the type A (all nearst neighbours (nn) are Fe atoms) and decrease for the type B (nn are Fe, Si and Al atoms). The most affected metal orbitals are Fe 4s and 4p. In the case of the hollow site the surface Fe–Fe bond is weakened after Se adsorption. A Fe–Se bond is developed at all coverages in both sites being the most important on top (dFe–Se = 2.23 Å, OP: 0.774 at 1/4 ML). The first and second layer Fe–Fe bond increase at 1/4 ML and decrease at 1/2 and 1 ML. Small Se–Se bonding interaction appear at 1/2 ML and increase noticeable for 1 ML. For the top site, the Se–Se bond appears at all coverage. The Fe–Fe surface bonds also decrease its strength with respect to the clean surface at all coverage. The first and second layer Fe–Fe bond increase at all coverage.